THE IMAGE OF THE AUTHOR IN THE ARTICLES (THEODORE DREISER) - Soybnazarov , Navruzbek Mashrabboy o‘g‘li (Innovative Development in Educational Activities, 2023)
The article is devoted to the analysis of the image of the author in the journalistic work of T. Dreiser. The study of journalism helps to determine the position of the writer regarding the political, historical, aesthetic and other phenomena of our time. Therefore, special attention in this article focuses on how the author's "I" is revealed at the compositional and problem-thematic levels, which is especially important when considering the problem of the fate of art in America at the turn of the 19th-20th centuries. Such approach to the image of the author in journalism makes it possible to find new parallels and meanings in the subsequent reference to the literary works of the writer.